Implementation of History Teacher Competencies at SMA Negeri 2 Dumai City - Mariani, Sakkot; Bunari, Bunari; Al Fiqri, Yanuar (Journal of Education Technology Information Social Sciences and Health, 2024)
A professional teacher does not only master one competency, but to be a professional teacher he must be able to master four competencies. History teachers should develop these competencies which are related to core competency (KI) 3 with the basic competencies contained therein instilling historical values. This research was conducted at SMA Negeri 2 Dumai City. The type of research used was qualitative research. The data collection methods used in this research are field observations, interviews and documentation. The data analysis techniques used in this research are data reduction, data display, and conclusion drawing. The research approach used is a descriptive qualitative research approach. The findings and discussion in this research are firstly the perspective of History Teachers at SMA Negeri 2 Dumai City regarding the importance of teacher competency and teacher competency that has been implemented well, secondly the implementation of history teacher competency at SMA Negeri 2 Dumai City, and thirdly the obstacles experienced in implementation Competency of history teachers at SMA Negeri 2 Dumai City. The first conclusion is that the teacher's perspective regarding the competence of history teachers at SMA Negeri 2 Dumai City is of the opinion that teacher competence is very important and has been well implemented. Secondly, the implementation of history teacher competence at SMA Negeri 2 Dumai City includes pedagogical competence, personality competence, social competence and professionalism competence, then the third is the obstacles experienced in implementing history teacher competence at SMA Negeri 2 Dumai City, including mastering the characteristics of students related to the teacher's ability to understand the condition of students, the curriculum transition adjustment period (the 2013 curriculum became the independent curriculum), the lack of numbers tools that support learning media, increasing professionalism for history teachers who have not participated in the PPPK program, apart from that the MMP is running ineffectively, and also obstacles in the lack of enthusiasm, attention and care of teachers in caring for students with diverse characteristics.